ANTIHYPERLIPIDEMIC PROPERTY OF BOERHAVIA DIFFUSA LEAF EXTRACT IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Ccs, Vasundhara; Devi S, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The aim of the present research was to evaluate the antidiabetic, hyperlipidemic, and histopathological analysis in streptozotocin-induced diabetic rats (60 mg/kg body weight) using the ethanolic extract of leaves of Boerhavia diffusa (ELBD) (500 mg/kg body weight). Method: The rats were orally administered with the leaf extract for 45 days. Fasting blood was collected at the end of the experimental period by cardiac puncture to carry out the biochemical parameters, the organs such as liver, kidney, and pancreas were also excised to perform the histopathological analysis by fixing in 10% formalin solution. Results: Oral administration with the leaf extract resulted in decrease in the levels of blood glucose, with a concomitant increase in their body weight. The extracts also produced a significant decrease in the lipid levels when compared with the diabetic groups. Moreover, the extracts also exerted a favorable effect on the histopathological changes of liver, pancreas, and kidney. Conclusion: The results of the present study revealed that the ELBD possess antidiabetic and antihyperlipidemic properties. These effects may be due to the presence of bioactive components justifying its ethnomedical use.